A Note on Accidents Involving Autonomous Vehicles: Interdependence of Event Data Recorder, Human-Vehicle Cooperation and Legal Aspects. Issue 34 (2019) - Martinesco, Andrea; Netto, Mariana; Neto, Arthur Miranda; Etgens, Victor H.
Abstract: Following the increase of automation levels in personal and public vehicles in the last decades, this note aims to discuss interdisciplinary investigation required to address criminal liability in case of an accident involving autonomous vehicles. Lawyers need from technicians definitions of automation levels. Each automation level requests differently the driver generating the need for related psychological and ergonomics studies. Finally, in the case of an accident, an Event Data Recorder (EDR) is of vital importance to reconstruct the events to the lawyers.